(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Smokingis an important public healthproblem of the present time. It is responsible for high disease burden and mortality among all age groups. Adolescents are rapidly growing and developing young children into adults and get easily indulge into smoking. Many factors contribute to start smoking in adolescent period. Aims &Objectives: To find out the prevalence of smoking among adolescents aged 14-19 years; to identify the factors responsible for smoking; and to find out association between smoking and various factors among adolescents. Methodology: Study Design: Cross-sectional survey. Study Setting: Union Council Maingri, Tehsil Shakargarh, District Narowal. Study Duration:- One month. Study Population: All the adolescents living in the union council Maingri. Sample Size: 300 adolescents aged 14-19 years were selected as study participant by simple random method. Results: Three-hundred adolescents were selected as study participants.Their mean age and SD was 16.63 ± 1.80years. 27.0% adolescents were smokers. Among 22 adolescents who were not attending school, 21 (95.5%) were smokers. Among 72 adolescents who were working, 58 (80.6%) were smokers. Among 135 adolescents whose fathers were smokers, 67 (49.6%) were smokers. Among 37 adolescents whose brothers were smokers, 28 (75.7%) were smokers. Among 62 adolescents whose friends were smokers, 59 (95.2%) were also smokers.Results showed significant association between adolescents smoking behavior and their schooling, working outside homes, parental and family smoking, smoking of friends and number of friends. Conclusion:Smoking of family members and friends had great influence on adolescents. Parents and teachers should play their significant roles in preventing adolescents from smoking through health education.